Antithrombotic Therapy for Aortic Aneurysms: A Systematic Review and Meta-Analysis. (November 2022) - Wong, Kitty H.F.; Zlatanovic, Petar; Bosanquet, David C.; Saratzis, Athanasios; Kakkos, Stavros K.; Aboyans, Victor; Twine, Christopher P.
Abstract : Objectives: The role of antithrombotic therapy in the management of aortic and peripheral aneurysms is unclear. This systematic review and meta-analysis aimed to assess the impact of antithrombotics on clinical outcomes for aortic and peripheral aneurysms. Methods: Medline, Embase, and CENTRAL databases were searched. Randomised controlled trials and observational studies investigating the effect of antithrombotic therapy on clinical outcomes for patients with any aortic or peripheral artery aneurysm were included. Results: Fifty-nine studies (28 with antiplatelet agents, 12 anticoagulants, two intra-operative heparin, and 16 any antithrombotic agent) involving 122 102 patients were included. Abdominal aortic aneurysm (AAA) growth rate was not significantly associated with the use of antiplatelet therapy (SMD –0.36 mm/year; 95% CI –0.75 – 0.02; p  = .060; GRADE certainty: very low). Antithrombotics were associated with increased 30 day mortality for patients with AAAs undergoing intervention (OR 2.30; 95% CI 1.51 – 3.51; p < .001; GRADE certainty: low). Following intervention, antiplatelet therapy was associated with reduced long term all cause mortality (HR 0.84; 95% CI 0.76 – 0.92; p < .001; GRADE certainty: moderate), whilst anticoagulants were associated with increased all cause mortality (HR 1.64; 95% CI 1.14 – 2.37; p  = .008; GRADE certainty: very low), endoleak within three years (OR 1.99; 95% CI 1.10 – 3.60; p  = .020; I 2  = 60%; GRADE certainty: very low), and an increased re-intervention rate at one year (OR 3.25; 95% CI 1.82 – 5.82; p < .001; I 2  = 35%; GRADE certainty: moderate). Five studies examined antithrombotic therapy for popliteal aneurysms. Meta-analysis was not possible due to heterogeneity. Conclusions: There was a lack of high quality data examining antithrombotic therapy for patients with aneurysms. Antiplatelet therapy was associated with a reduction in post-intervention all cause mortality for AAA, whilst anticoagulants were associated with an increased risk of all cause mortality, endoleak, and re-intervention. Large, well designed trials are still required to determine the therapeutic benefits of antithrombotic agents in this setting.